What adults in rural South Asia eat and when they eat it: Evidence from Bangladesh, India, and Nepal - Scott, Samuel P.; Patwardhan, Sharvari; Ruel, Marie T.; Chakrabarti, Suman; Neupane, Sumanta; Manohar, Swetha; Moursi, Mourad; Menon, Purnima (2025)
Background Poor diets pose a threat to all forms of malnutrition and diet-related noncommunicable diseases (NCDs). Data on dietary patterns are scarce in South Asia.